The effects of the C-terminal amidation of mastoparans on their biological actions and interactions with membrane-mimetic systems - Silva, Alessandra. V. R. da [UNESP]; De Souza, Bibiana M. [UNESP]; Santos Cabrera, Marcia P. dos [UNESP]; Dias, Nathalia B. [UNESP]; Gomes, Paulo C. [UNESP]; Ruggiero Neto, Joao [UNESP]; Stabeli, Rodrigo G.; Palma, Mario S. [UNESP] (Elsevier B.V., 2014)
Polycationic peptides may present their C-termini in either amidated or acidic form; however, the effects of these conformations on the mechanisms of interaction with the membranes in general were not properly investigated up to now. Protonectarina-MP mastoparan with an either amidated or acidic C-terminus was utilized to study their interactions with anionic and zwitterionic vesicles, using measurements of dye leakage and a combination of H/D exchange and mass spectrometry to monitor peptide-membrane interactions. Mast cell degranulation, hemolysis and antibiosis assays were also performed using these peptides, and the results were correlated with the structural properties of the peptides. The C-terminal amidation promotes the stabilization of the secondary structure of the peptide, with a relatively high content of helical conformations, permitting a deeper interaction with the phospholipid constituents of animal and bacterial cell membranes. The results suggested that at low concentrations Protonectarina-MP interacts with the membranes in a way that both terminal regions remain positioned outside the external surface of the membrane, while the alpha-carbon backbone becomes partially embedded in the membrane core and changing constantly the conformation, and causing membrane destabilization. The amidation of the C-terminal residue appears to be responsible for the stabilization of the peptide conformation in a secondary structure that is richer in alpha-helix content than its acidic congener. The helical, amphipathic conformation, in turn, allows a deeper peptide-membrane interaction, favoring both biological activities that depend on peptide structure recognition by the GPCRs (such as exocytosis) and those activities dependent on membrane perturbation (such as hemolysis and antibiosis). (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Mastoparan; Antimicrobial peptide; H/D exchange; Mass spectrometry; Peptide-membrane interaction; Peptidomics